2020
DOI: 10.13106/jafeb.2020.vol7.no11.367
|View full text |Cite
|
Sign up to set email alerts
|

Linking Emotional Brand Attachment and Sales Promotion to Post-Purchase Cognitive Dissonance: The Mediating Role of Impulse Buying Behavior

Abstract: The primary objective of this research is to develop a better understanding of consumer's post-purchase psychological state by examining the influence of sales promotion and emotional brand attachment on post-purchase cognitive dissonance, taking into account the mediating role of impulse buying behavior. The current study addresses several gaps in literature. Firstly, it is hard to find the direct impact of sales promotion and emotional brand attachment on post-purchase cognitive dissonance. Secondly, to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 58 publications
0
27
0
4
Order By: Relevance
“…Profit-making programs seek to compensate individuals for their sacrifices by providing subsidies. Previous research has found that profitmaking strategies can only be successful for a limited amount of time unless they are long-term (Handgraaf et al, 2013;Frederiks et al, 2015;Akbar et al, 2020). As a result, profitmaking solutions may not successfully drive energy-saving behavior (ESB) in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…Profit-making programs seek to compensate individuals for their sacrifices by providing subsidies. Previous research has found that profitmaking strategies can only be successful for a limited amount of time unless they are long-term (Handgraaf et al, 2013;Frederiks et al, 2015;Akbar et al, 2020). As a result, profitmaking solutions may not successfully drive energy-saving behavior (ESB) in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…studies have investigated the factors that affect post-purchase cognitive dissonance (e.g.,Akbar et al, 2020;Al-Adamat & Al- Adamat, 2019;Keng & Liao, 2013;Kocamaz & Karadeni ż, 2020;Shahin Sharifi & Rahim Esfidani, 2014;Wilkins et al, 2016). However, the effects of future orientation, holistic thinking, and risk perception on post-purchase cognitive dissonance-revealed in this studyhave not been investigated.…”
mentioning
confidence: 77%
“…A significant part of existing literature explores how cognitive dissonance can be measured, managed, or dealt with (e.g., Bawa & Kansal, 2008; Revelle, 2010; Sweeney et al., 2000). Few studies have investigated the factors that affect post‐purchase cognitive dissonance (e.g., Akbar et al., 2020; Al‐Adamat & Al‐Adamat, 2019; Keng & Liao, 2013; Kocamaz & Karadeni̇z, 2020; Shahin Sharifi & Rahim Esfidani, 2014; Wilkins et al., 2016). However, the effects of future orientation, holistic thinking, and risk perception on post‐purchase cognitive dissonance—revealed in this study—have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations